Distinct white matter integrity in glutamic acid decarboxylase and voltage‐gated potassium channel‐complex antibody‐associated limbic encephalitis. (8th January 2016) - Wagner, Jan; Schoene‐Bake, Jan‐Christoph; Witt, Juri‐Alexander; Helmstaedter, Christoph; Malter, Michael P.; Stoecker, Winfried; Probst, Christian; Weber, Bernd; Elger, Christian E.
Summary: Objective: Autoantibodies against glutamic acid decarboxylase (GAD) and the voltage‐gated potassium channel (VGKC) complex are associated with distinct subtypes of limbic encephalitis regarding clinical presentation, response to therapy, and outcome. The aim of this study was to investigate white matter changes in these two limbic encephalitis subtypes by means of diffusion tensor imaging (DTI). Methods: Diffusion data were obtained in 14 patients with GAD antibodies and 16 patients with VGKC‐complex antibodies and compared with age‐ and gender‐matched control groups. Voxelwise statistical analysis was carried out using tract‐based spatial statistics. The results were furthermore compared with those of 15 patients with unilateral histologically confirmed hippocampal sclerosis and correlated with verbal and figural memory performance. Results: We found widespread changes of fractional anisotropy and all diffusivity parameters in GAD‐associated limbic encephalitis, whereas no changes were found in VGKC‐complex–associated limbic encephalitis. The changes observed in the GAD group were even more extensive when compared against those of the hippocampal sclerosis group, although the disease duration was markedly shorter in patients with GAD antibodies. Correlation analysis revealed areas with a trend toward a negative correlation of diffusivity parameters with figural memory performance located mainly in the right temporal lobe in the GAD group as well. Significance: The present study provides further evidence that, depending on the associated antibody, limbic encephalitis features clearly distinct imaging characteristics by showing widespread white matter changes in GAD‐associated limbic encephalitis and preserved white matter integrity in VGKC‐complex–associated limbic encephalitis. Furthermore, our results contribute to a better understanding of the specific pathophysiologic properties in these two subforms of limbic encephalitis by revealing that patients with GAD antibodies show widespread affections of white matter across various regions of the brain. In contrast to this, the inflammatory process seems to be more localized in VGKC‐complex–associated limbic encephalitis, primarily affecting mesiotemporal gray matter.